Patterns and Trends of Respiratory Diseases in Indonesian Hajj Pilgrims in Mecca: 2024 Descriptive Study - Susetyo, Rahma Rufaida (INDOGENIUS, 2025)
Background and Objective: Respiratory diseases are a major health problem for Indonesian Hajj pilgrims in Mecca, triggered by extreme environmental factors such as high temperatures (39-43°C), crowding, and air pollution. Changes in physical activity and dust exposure also play a role, especially in the elderly and those with comorbidities. Data from the Ministry of Health shows that >50% of Hajj pilgrims experience respiratory problems, with pneumonia, bronchitis, and asthma as common diagnoses, particularly after the peak of the Hajj pilgrimage. This study aims to analyze the patterns and trends of respiratory diseases among Indonesian Hajj pilgrims in Mecca in 2024. Methods: This descriptive-analytic study uses secondary data from the registration of regular Hajj pilgrims at the KKHI Mecca in 2024 (1445 H). The total sample consists of 1962 Hajj pilgrims. Data were analyzed quantitatively using descriptive. Results: The majority of Hajj pilgrims seeking treatment were male (55.4%) and aged >61 years (65.3%). Pneumonia was the most common respiratory disease (62%), followed by COPD (11.8%), asthma (4.3%), and ARI (8.1%). Risk factors included old age, extreme weather changes, physical fatigue, and air pollution. The majority of cases were treated on an outpatient basis at the KKHI Mecca (61.1%). Conclusion: Pneumonia is a major health problem among Indonesian Hajj pilgrims in Mecca. Old age is an important risk factor. Comprehensive prevention and treatment efforts are needed, including health education, awareness of medical personnel, and further research. This study provides valuable information for the development of more effective Hajj health policies.